Analysis of Element Failures in Active Incoherent Microwave Imaging Arrays Using Noise Signals - Vakalis, Stavros; Nanzer, Jeffrey A. (IEEE microwave and wireless components letters, 2019)
An analysis of the effects of receiver element failures in active incoherent microwave imaging arrays is presented. Active incoherent microwave imaging is a new imaging method that uses transmission of noise signals combined with a sparse array using interferometric processing. In this method, the failure of individual receiver array elements results in gradual degradation of the image, rather than losses of pixels. This letter analyzes the image degradation in terms of the root-mean-square error (RMSE) of the image formed with randomly failed elements compared to the image formed with all elements. Measured data using a 5.85-GHz experimental imaging system show that RMSE below 10% can be maintained with failure rates extending up to 25%. Modeled image formation performance and the sidelobe level of the point spread function is shown to track well with the measured data for up to 50% element failures, indicating a robust method for predicting imaging performance.